Implementasi Mendidik Anak Dengan Keteladanan Dan Cinta - Samosir, Rotua; Simanungkalit, Siska; Silitonga, Ester; Gulo, Desmawati (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2023)
It is very important for parents to educate children by example and love. Since the beginning, parents are required to have a vision and mission in educating children. Because, if it gets wrong educated, a problem could arise in the future. According to Arin's notes, what you as a parent must remember is that children who are born into the world already have the title of khoiru ummah or the best people who invite goodness. Then, what needs to be remembered again is what has been explained in QS. An-Nisa (9), "And let fear (of Allah) those who, if they leave weak offspring behind them, they are worried about their welfare."